Characterization of the cellulosic cell wall (Blackwell Pub., 2006)
This volume brings together a broad array of scientific expertise to focus on the characterization and utilization of cellulosic materials. Researchers from Austria, Germany, Sweden, Japan, New Zealand, Australia, and the U.S. explore many facets of the plant cell wall, from its fundamental structure and its manipulation via molecular biology to its application in composite materials. Exciting applications of near infrared spectroscopy, x-ray diffraction, confocal microscopy, and molecular coupling as a viscoelastic probe provide new insights into the ultrastructure and properties of cellulosic materials.